Faktor-Faktor Yang Mempengaruhi Indeks Pembangunan Manusia (IPM) Di Provinsi Jawa Timur - Karonika Sihite; Fatimah Fatimah; Santi monika sagala; Asnidar Asnidar; Ahmad ridha (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2024)
This research aims to analyze the influence of GDP per capita, poverty, Gini Index, and Economic Growth Rate on the Human Development Index (HDI) in East Java Province during the 2013-2022 period. The analytical method used is multiple linear regression using secondary data. The results of the analysis show that partially, GDP per capita has a positive and significant effect on HDI, while the Growth Rate and Gini Index have a negative and insignificant effect on HDI in East Java Province. conclusion provides a comprehensive picture of the factors that influence HDI in the region, and the implications can be used to support development policy decision making in East Java Province.